Socioeconomic factors predicting outcome in surgically treated carpal tunnel syndrome: a national registry-based study - Zimmerman, Malin (Sci Rep, 2021)
The study aimed to investigate socioeconomic factors in patients with carpal tunnel syndrome (CTS) and to evaluate their impact on outcome following open carpal tunnel release (OCTR). Data from the National Quality Register for Hand Surgery were combined with socioeconomic data (marital status, education level, earnings, migrant status, occupation, sick leave, unemployment, and social assistance) from Statistics Sweden to evaluate OCTRs performed from 2010 to 2016 (total 10,746 OCTRs). Patients completed QuickDASH (short version of Disabilities of Arm, Shoulder and Hand) questionnaires preoperatively (n = 3597) and at three (n = 2824) and 12 months (n = 2037) postoperatively. The effect of socioeconomic factors on QuickDASH scores was analyzed with linear regression analysis. Socioeconomically deprived patients scored higher on the QuickDASH on all occasions than patients with higher socioeconomic status. Being widowed, having a low education level, low earnings, immigrant status, frequent sick leave and dependence on social assistance all increased the postoperative QuickDASH score at 12 months. The change in total score for QuickDASH between preoperative and 12 months postoperatively did not vary between the groups. We conclude that such factors as being widowed, having a lower education level, low earnings, immigrant status, frequent sick leave and social assistance dependence are associated with more symptoms both before and after OCTR for CTS, but these factors do not affect the relative improvement in QuickDASH.